The effect of a strategy based on the communicative approach in reading comprehension for tenth grade students in Jordan - Al-mousah, Maryam Hammad Abdallah (Journal of Educational and Psychological Sciences, 2020)
The study aimed to reveal the effect of a strategy based on the communicative approach in reading comprehension for tenth grade students in Jordan. To achieve the aims of the study, a test was designed to measure reading comprehension skills, and its validity and reliability were confirmed, The semi-experimental design was adopted, as the experimental group consisting of (25) students was studied according to the strategy based on the communicative approach, and the control group consisting of (25) students was studied in the usual way, The test was applied to the two groups before and after the experiment, The results of the ANCOVA analysis showed that there was a statistically significant difference at (α≤05,0) between the two groups due to the strategy based on the continuous approach in improving reading comprehension, and for the benefit of the experimental group. The study recommended employing a communicative approach in teaching the Arabic language topic, and conducting other similar studies in different educational stages and with new changes.
Keywords: communication; oriented strategy; reading comprehension; basic tenth grade